Rewiring photosynthetic carbon flow: Engineered cyanobacterial factories for sustainable carbohydrate production and carbon-negative biomanufacturing - Bai, Xinyi; Zhang, Guangbao; Libo Xu; Kang Li; Mengjun Zhang; Yi Huang (Bioresource Technology, 2025)
Cyanobacteria are promising platforms for light-driven carbon fixation and carbohydrate biosynthesis. However, optimization strategies that focus solely on carbon allocation are insufficient to achieve substantial improvements in yield and sustainability. Here, Synechococcus elongatus PCC 7942 was engineered to enhance sucrose production by simultaneously increasing total carbon input and reinforcing the artificial sink. The engineered strain secreted 5.821 g L−1 sucrose, which was 27.4 times higher than the wild-type. Transcriptomic analysis revealed upregulation of abundant genes involved in carbon fixation, sucrose biosynthesis, and electron transport chains. Furthermore, a synthetic light-driven consortium was established to directly convert CO2 into value-added compounds. This system produced 323.5 mg L−1 polyhydroxybutyrate, reducing CO2 emissions by 12.4 g per g of polyhydroxybutyrate compared to conventional heterotrophic processes. These findings highlight the potential of cyanobacteria-based systems for carbon-negative biomanufacturing, demonstrating their role in advancing sustainable carbohydrate and biochemical production while exemplifying circular bioeconomy principles.